Perlindungan Hukum terhadap Kreditur dalam Pelaksanaan Penghapusan Kredit Macet UMKM pada Bank BUMN - Yeni Mardiah Lubis; Mahmul Siregar; Syarifah Lisa Andriati (CV WAHANA PUBLIKASI, 2026)
The elimination of bad loans for micro, small, and medium enterprises (MSMEs) is an instrument for resolving non-performing loans that aims to maintain banking stability and support the sustainability of MSME financing. However, its implementation still faces problems related to legal certainty and legal protection for banks as creditors. This study aims to analyze the regulation of MSME bad loans in Indonesia, its implementation at PT Bank XXX, as well as the form of legal protection for banks in its implementation. The research method used is empirical normative legal research with a statutory approach and a case approach. Data was obtained through literature studies and interviews, then analyzed qualitatively using legal certainty theory and legal protection theory. The results of the study show that the elimination of MSME bad loans has an adequate legal basis, but has not fully provided legal certainty due to regulatory inconsistency and the absence of comprehensive technical guidelines. At PT Bank XXX, the implementation of credit write-off is carried out according to the principle of prudence by prioritizing restructuring, receivables recovery, and insurance claims before write-off. Legal protection for banks is realized through the application of the principle of prudence, the use of collateral and credit insurance, and the maintenance of bank billing rights. Therefore, it is necessary to harmonize regulations and strengthen legal certainty to support the effectiveness of the implementation of the elimination of bad loans for MSMEs.